Creating value chains: the role of relationship development. Issue 6 (6th June 2016) - Hastings, Kathleen; Howieson, Janet; Lawley, Meredith
Abstract : Purpose: – The purpose of this paper is to identify the key characteristics of business-to-business relationships in the early stages of the relationship that will influence the successful creation of value chains. Identification of these characteristics will provide a decision-making tool for continuing the effective development of the value chain process. Design/methodology/approach: – Key characteristics necessary to develop strong relationships were identified from the literature. These characteristics will assist the relationship to evolve into a long-standing mature relationship. An expert panel evaluated four value chain analysis (VCA) case studies against these characteristics in order to identify patterns in relationships that could explain the varied performance of these cases. Findings: – In total, 15 relational characteristics were identified that must be present in the engagement stage before initiating the next step in the VCA process. An assessment of the activities associated with pre-relationships and early relationships within the value chain provide a strong indication of the chains ability to conduct successful VCA. Research limitations/implications: – This research furthers the understanding of value chains and adds an important and novel contribution of relationship characteristics to the early stages of relationship development within value chains. Originality/value: – The application of relationship development to the engagement of value chains is an extension to the VCA literature. Relationships are a proven foundation component of successful value chains, and yet relationship development research from business-to-business marketing has not been well incorporated into the value chain literature. The framework proposed in this paper facilitates an assessment on the level of chain engagement and readiness to take the next step in the value chain process, thus making a valuable practical contribution.